Strategi Penyelesaian Konflik Lahan antara Perusahaan dengan Masyarakat melalui Pendekatan Sosiologi Hukum - Mohd. Yusuf Daeng M.; Deki Wiranata Adha; Egy Wahyudi; Juni Kasmira; Geofani Milthree Saragih (Departement of Mathematics Education, 2023)
Conflict is usually related to other individuals or groups, therefore it is often called social conflict. Based on Law Number 7 of 2012 concerning Handling of Social Conflict, what is meant by Social Conflict is violent feuds and/or physical clashes between two or more community groups that take place within a certain time and have wide-reaching impacts resulting in insecurity and social disintegration thereby disrupting social stability. national and impede national development. Sociologists argue that the root of the emergence of conflict is the existence of social, economic, political relations whose roots are the struggle over sources of ownership, social status and power whose availability is very limited with unequal distribution in society. This type of research is normative legal research with a case, regulation, and analysis approach. This study aims to provide a strategy for resolving legal disputes between companies and the community through a legal sociology approach.